Trans-Pacific Partnership (TPP) Competition-Asian Infrastructure Investment Bank (AIIB) and its Effect on Balance of Power AS-PRC - Priangani, Ade (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to provide a description and confirmation concerning the strategy focused on the Asia Pacific region competition. The rebalancing strategy is evident from the US participation in TPP, the US presence to the Asia Pacific region was triggered by the increasing capability of China that became a new power in the region both in the economy, diplomacy, and military. The method used in conducting this research is a description that aims to describe the phenomenon in terms of the influence of the TPP-AIIB competition against the US-China Balance of Power. Data is obtained from relevant documents, study results and mass media, while primary data is from observation. Data are analyzed based on the theory and concept of international relations and being interpreted. The results of this research show that the forms of competition TPP-AIIB in the form of a US policy "pivot to Asia" The strategy is a concentration of foreign policy direction which is a continuation of the national interests of the United States -Pacific Partnership (TPP) is more potential in the counterbalance of US dominance in the Asia Pacific region.